1984
DOI: 10.1002/gj.3350190305
|View full text |Cite
|
Sign up to set email alerts
|

Arenig trace fossils from the Salamanca area, western Spain

Abstract: Trace fossils are recorded at two localities from the ‘Armorican Quartzite’ (Lower Ordovician) in the Salamanca area, western Spain. Sixteen ichnospecies, belonging to twelve ichnogenera, are described; all ichnospecies occur in the upper part of the unit, only four in the lower part. The ichnogenera comprise Arthrophycus, Cruziana, Daedalus, Didymaulichnus, Diplichnites, Diplocraterion, cf. Gor‐. dia, Monomorphichnus, Muensteria, Palaeophycus, Planolites, and Rusophycus. The presence of Cruziana furcifera, C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…This sedimentary unit is composed of white orthoquartzitic layers containing Cruziana and was deposited along the peri-Gondwana continental margin during a transgressive event. It is attributed to the Floian stage of the Lower Ordovician on the basis of its fossil and ichnofossil content (Moreno et al 1976;Pickerill et al 1984). …”
Section: Geological Settingmentioning
confidence: 99%
“…This sedimentary unit is composed of white orthoquartzitic layers containing Cruziana and was deposited along the peri-Gondwana continental margin during a transgressive event. It is attributed to the Floian stage of the Lower Ordovician on the basis of its fossil and ichnofossil content (Moreno et al 1976;Pickerill et al 1984). …”
Section: Geological Settingmentioning
confidence: 99%
“…Meniscate burrows reported from the mid-Silurian Grampians Group of Western Australia probably formed in a fully marine setting (George, 1994;contra Gouramanis et al, 2003). Elsewhere (2000), Gand et al (1997), Germs (1972), Goldring and Pollard (1995), Graham and Pollard (1982), Hakes (1976), Han and Pickerill (1994), Häntzschel (1975), Hunter and Lomas (2003), Knaust (2004), Kulkarni and Borkar (2014), Kumpulainen et al (2006), Maples and Archer (1987), Maples and Suttner (1990), Martino (1989), Mikulas (1993), Minter et al (2007), Morrissey and Braddy (2004), Narbonne (1984), O'Sullivan et al (1986), Pearson (1992), Pickerill (1991), Pickerill (1992), Pickerill et al (1987), Pickerill et al (1984), Prescott et al (2014), Qi et al (2012), Savoy (1992), Smith (1993), Stephenson and Gould (1995), Tanoli and Pickerill (1989), Thomas and Smith (1998), Tunbridge (1984) and Weber and Braddy (2004). they are reported in Late Silurian-Early Devonian deposits from transitional continental-marine settings in the Ringerike Group of Norway, Tumblagooda Sandstone of Western Australia, and Mereenie Sandstone of the Northern Territory, Australia (Trewin and McNamara, 1994;Davies et al, 2006 Gouramanis and…”
Section: Discussion Of Silurian Trace Fossilsmentioning
confidence: 99%
“…It therefore remains unclear whether the transition of one Cruziana ichnotaxon into the other as mentioned by Mángano, Buatois & Moya (2001) is partly due to preservational aspects of the Argentinian material, or if it really represents an intergradation of two ichnospecies. But even though a transition should exist between C. furcifera and C. goldfussi, intermediate specimens are the exception rather than the norm and should not lead to the abandonment of the ichnospecies concept for the Cruziana rugosa Group (Pickerill, Romano & Meléndez, 1984). It is concluded that the ichnotaxonomic characteristics allow a clear distinction between the four members of the C. rugosa Group in well-preserved material, and therefore, based on the excellently preserved Bolivian Cruziana specimens, Seilacher's (1970) ichnospecies are here considered valid.…”
Section: B Is a Clear Taxonomic Differentiation Of Four Ichnospecimentioning
confidence: 99%